Genetic diversity of Colombian sheep by microsatellite markers (2016)
RESUMEN: In Colombia the sheep production systems are managed under extensive conditions and mainly correspond to peasant production systems so their genetic management has led to increased homozygosity and hence productivity loss. The aim of this study was to determine the genetic diversity in 549 individuals corresponding to 13 sheep breeds in Colombia, using a panel of 11 microsatellite molecular markers. One hundred and fifty seven alleles were found (average of 14.27 alleles/locus), with a range of observed and expected heterozygosity from 0.44 to 0.84 and 0.67 to 0.86, respectively. Thirty-three of 143 Hardy Weinberg tests performed showed significant deviations (p < 0.05) due to a general lack of heterozygous individuals. The Fis ranged from 0.01 in Corriedale to 0.15 for the Persian Black Head breed, suggesting that there are presenting low to moderate levels of inbreeding. Overall, Colombian sheep showed high levels of genetic diversity which is very important for future selection and animalbreeding programs.